The emergence of net-centric computing : network computers, Internet appliances, and connected PCs - Cole, Bernard Conrad (Prentice Hall PTR, 1999)
The traditional PC is history: Net-centric computing is the future. But what form will it take? Computing appliances, "connected PCs," Web-enabled set-top boxes, Webphones, Internet-connected wireless communicators, or Java-based network computers? All of them - or something else entirely? What challenges face professionals who want to build, plan for, or invest in these new systems?